Towards conceptualisation of low-carbon supply chain - Norma, Mohter; Fernando, Yudi (Inderscience Publisher, 2025)
In this study, we urged manufacturers to practise low-carbon (LC) throughout their supply chain (SC). This paper also highlighted the need for LC practices in the supply chain. A few elements have been discovered to support the necessity for LC practices. For instance, changes in consumer preferences for low-carbon products, low-carbon awareness among customers, stakeholder demand for sustainability practices in the company and government policies are the factors that influence the LC practices in supply chain. However, there are still many manufacturers who need to be educated about this necessity and change their production process due to financial constraints. LC should begin with the supply chain due to supply chain activities contribute significantly to carbon emissions. Low carbon supply chain practices are an effective strategy for manufacturers to reduce their carbon footprint and obtain an advantage over their competitors. Manufacturing can boost revenue, improve company’s reputation, and environmentally friendly.